Frontal polymerization of superabsorbent polymers based on vermiculite with slow release of urea. Issue 1 (11th July 2016) - Yuan, Huan; Qiu, Zhaoxia; Qiu, Haixia; Zhang, Ruobing
Abstract : Poly(acrylic acid‐co‐acrylamide)/sodium carboxymethyl cellulose/vermiculite (VMT) superabsorbent polymers (SAPs) were prepared by frontal polymerization (FP), a kind of polymerization model characterized by short reaction times and low‐energy consumption. The effects of VMT content and monomer ratios on frontal parameters and water absorbency were investigated. Due to the good heat insulation property of VMT, the propagating front still sustained at high VMT concentrations (over 30%). The preparation of SAPs with high VMT‐loading via FP has advantages of low energy consumption and low materials prices, decreasing the cost of SAPs effectively. SAPs with slow‐release fertilizer (SSRF) were obtained by embedding urea into their networks during the FP process. The addition of urea not only endows SAPs with slow release function of urea (more than 30 days in soil), but also increases their water absorbency (by 17.4%). The effects of obtained SSRF on tall fescue seeds germination and growth were studied. Compared with the control group, the germination rate and vigor index of tall fescue seeds applied SSRF with 10% urea increased by 17.5 and 80.2%, respectively. POLYM. ENG. SCI., 57:69–77, 2017. © 2016 Society of Plastics Engineers